Rapid Diagnosis and Treatment of Patients with Acute Type A Aortic Dissection and Malperfusion Syndrome May Normalize Survival to that of Patients with Uncomplicated Type A Aortic Dissection - Bin Mahmood, Syed Usman; Mori, Makoto; Luo, Jiajun; Zhang, Yawei; Safdar, Basmah; Ulrich, Andrew; Geirsson, Arnar; Elefteriades, John A.; Mangi, Abeel A. (AORTA, 2019)
Objectives Malperfusion syndrome in the setting of acute Type A dissection (ATAD) is typically associated with poor prognosis. We evaluated the contemporary outcomes of patients with ATAD presenting with and without malperfusion syndrome who underwent aortic surgery.Methods We performed a single-center, retrospective review of 103 consecutive patients that underwent surgery for ATAD. The cohort was dichotomized by patients with and without malperfusion syndromes. Multivariate and bivariate analyses were performed to evaluate association between the presence of malperfusion syndrome and operative outcomes.Results A total of 29 (28.1%) patients presented with malperfusion syndrome. The 30-day mortality for patients presenting with and without malperfusion was 13.7 and 9.4%, respectively (p = 0.49). Patients with malperfusion syndrome had a shorter mean admission-to-incision interval of 4.3 ± 2.5 hours compared with 6.3 ± 4.6 hours for those without malperfusion (p = 0.02). Difference in 30-day mortality for patients with and without malperfusion syndrome was found to be nonsignificant on multivariate regression analysis (odds ratio: 1.53; 95% confidence interval: 0.40–5.82, p = 0.49).Conclusions This series demonstrated that there was nonsignificant difference in early- or midterm outcomes for patients with and without malperfusion syndrome. Patients with malperfusion were taken to the operating room more rapidly than those without, which offers a potential explanation for the comparable outcome of the malperfusion cohort.
Keywords: Type A aortic dissection; malperfusion syndrome; ascending aortic replacement